2019
DOI: 10.1021/acs.chemmater.9b02263
|View full text |Cite
|
Sign up to set email alerts
|

A Lead-Free Hybrid Iodide with Quantitative Response to X-ray Radiation

Abstract: Single crystals of lead halide hybrid perovskites (e. g., CH3NH3PbI3 and CsPbBr3) have been developed as promising candidates for X-ray detection, owing to their excellent attributes including low trap density, high X-ray absorption cross section, and high carrier mobility. The toxicity of lead, however, is a potential bottleneck that hinders their device application toward green and sustainable competitors. Herein, we reported a new lead-free bismuth-iodide hybrid of (H2MDAP)­BiI5 (1, H2MDAP = N-methyl-1,3-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 52 publications
5
85
0
1
Order By: Relevance
“…This situation also occurs in similar compounds, such as (C 3 H 9 NI) 4 AgBiI 8 , [ 19 ] Cs 3 Bi 2 I 9 , [ 20 ] and (H 2 MDAP)BiI 5 . [ 21 ] In addition, the PDOS disclose that the valence band and conduction band origin is derived from I‐5p states, Bi‐6p and Ag‐4p, respectively (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…This situation also occurs in similar compounds, such as (C 3 H 9 NI) 4 AgBiI 8 , [ 19 ] Cs 3 Bi 2 I 9 , [ 20 ] and (H 2 MDAP)BiI 5 . [ 21 ] In addition, the PDOS disclose that the valence band and conduction band origin is derived from I‐5p states, Bi‐6p and Ag‐4p, respectively (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Although the single crystal had a high bulk resistivity of 10 10 Ω cm and even better X-ray attenuation capacity than CZT, the detector generated a low sensitivity of 1 μC Gy air −1 cm −2 , probably as a result of the relatively high trap density (10 11 cm −3 ) and relatively low carrier mobility (1.42 cm 2 V −1 s −1 ). 83 Similarly, 1D (DMEDA) BiI 5 (DMEDA is N,N 0 -dimethylethanediamine) was developed. By applying an extremely high electrical field of 494 V mm −1 perpendicular to the chain of BiI 6 octahedra that isolated by DMEDA cations, the detector showed a sensitivity of 72.5 μC Gy air −1 cm −2 and dark current of 30 nA cm −2 .…”
Section: Low-dimension Bismuth Based Halide Perovskitesmentioning
confidence: 99%
“…For example, Tao et al reported a single‐crystalline (H 2 MDAP)BiI 5 (H 2 MDAP denotes N‐methyl‐1,3‐diaminopropanium) based X‐ray detector. Although the single crystal had a high bulk resistivity of 10 10 Ω cm and even better X‐ray attenuation capacity than CZT, the detector generated a low sensitivity of 1 μC Gy air −1 cm −2 , probably as a result of the relatively high trap density (10 11 cm −3 ) and relatively low carrier mobility (1.42 cm 2 V −1 s −1 ) 83 . Similarly, 1D (DMEDA)BiI 5 (DMEDA is N,N′‐dimethylethanediamine) was developed.…”
Section: Materials Engineering Of Perovskite X‐ray Absorbermentioning
confidence: 99%
“…[19] reported a solution-grown 0D MA 3 Bi 2 I 9 SC with an X-ray detection S as high as 10,620 μC Gy air −1 cm −2 . Furthermore, hybrid perovskite (BA) 2 CsAgBiBr 7 SCs (2D) and (H 2 MDAP)BiI 5 SCs (1D) have been successfully grown from a solution, and S of 4.2 and 1 μC Gy air −1 cm −2 were obtained, respectively [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the high S for X-ray detection, bismuth-halide perovskites with low dimensional structures exhibit high resistivity and very low ionic migration. This results in extremely low dark currents at the pA level and no drift, which is beneficial for an extremely low detectable dose rate [20][21][22][23]25]. (45), and is only slightly smaller than that of (NH 4 ) 3 Bi 2 I 9 (48.3) and Cs 3 Bi 2 I 9 (57.7).…”
Section: Introductionmentioning
confidence: 99%